2015
DOI: 10.1159/000380875
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat Use Affects Brain Size and Structure in Intertidal Gobies

Abstract: The ecological cognition hypothesis poses that the brains and behaviours of individuals are largely shaped by the environments in which they live and the associated challenges they must overcome during their lives. Here we examine the effect of environmental complexity on relative brain size in 4 species of intertidal gobies from differing habitats. Two species were rock pool specialists that lived on spatially complex rocky shores, while the remainder lived on dynamic, but structurally simple, sandy shores. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 73 publications
4
38
0
Order By: Relevance
“…This is similar to patterns documented in other vertebrates where variation in brain size is closely correlated with ecology [Yopak et al, 2007;Yopak and Montgomery, 2008;Eifert et al, 2015;White and Brown, 2015]. For example, the brains of fresh water genera (e.g., Ichthyomyzon and Eudontomyzon ) were rel-atively smaller than those of their closest anadromous relatives ( Fig.…”
Section: Discussionsupporting
confidence: 84%
“…This is similar to patterns documented in other vertebrates where variation in brain size is closely correlated with ecology [Yopak et al, 2007;Yopak and Montgomery, 2008;Eifert et al, 2015;White and Brown, 2015]. For example, the brains of fresh water genera (e.g., Ichthyomyzon and Eudontomyzon ) were rel-atively smaller than those of their closest anadromous relatives ( Fig.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, all methods provide support for the theory that various fish species trade off neural investment in specific brain lobes depending on the environment in which they live. These data suggest that rock pool species require greater spatial learning abilities to navigate in their spatially complex environment, while sand-dwelling species, on the other hand, likely have reduced need for spatial learning due to their spatially simple habitat and a greater need for visual acuity (for further detail on brain lobe differences between species, see [White, 2015]). Therefore, it seems that for the species studied here -regardless of the method used -there is a guarantee to obtain fairly precise estimates of volume differences between the species for comparative purposes even if the volume estimates are not entirely accurate.…”
Section: Comparison Of Brain Assessment Methodologiesmentioning
confidence: 97%
“…A study by Ullmann et al [2010] looking at barramundi brain volumes found that the olfactory bulbs closely mimic the shape of idealised ellipsoids, while the shape of the telencephalon and optic tectum deviated from the elliptical shape and thus was overestimated by the ellipsoid method. Histology is a long-established method for calculating brain volumes and a considerable number of studies have utilised varying stereological techniques [Haug, 1986;Rosen and Harry, 1990;White, 2015]. However, histology is labour-intensive, time-consuming and provides only 2D views of brain areas ( table 3 ).…”
Section: Comparison Of Brain Assessment Methodologiesmentioning
confidence: 99%
See 2 more Smart Citations